ACL Tears: Contributing Factors and Preventive Strategies for the Home Health Care Professional—Part 1. (February 2015) - Shephard, Meredith K.; Hoover, Donald L.; Neelly, Kurt R.
This article addresses the scientific literature on contributing factors and preventive strategies for anterior cruciate ligament (ACL) injuries, and it offers suggestions home health care professionals may find useful in the prevention and rehabilitation of this injury. More specifically, this two-part article summarizes contemporary research on the functional anatomy of the knee, precipitating factors to ACL injuries, and current strategies in the rehabilitation of these injuries. Part 1—covered here—addresses the knee's functional anatomy and precipitating factors to ACL injuries noted in the scientific literature. Part 2—covered in a subsequent issue of Home Health Care Management & Practice ( HHCMP )—addresses contemporary trends evident in the peer-reviewed literature on the topic of the rehabilitation of ACL injuries.